Franco da Rocha-SP: memórias e histórias da cidade (1980-2010) - Reis, Adilson dos Santos (2011)
The present work analyzes the construction of the memoirs of the Municipal district of Franco of Rocha, located in Great São Paulo, and your relationship with the public representations of the city, whose, centralization was if constituting starting from the Psychiatric Hospital of Juqueri. With the relationships between histories and memoirs, initially, it problematizes works of local memorialists, news of the press and materials of popularization of the public power, looking for to identify which are the projects and memoirs that are configured while hegemonic in the city. In a second moment working with depositions, it interprets the residents' speeches, looking for to give visibility other histories and memoirs in dispute in the city. It brings for the dialogue the memories and these residents' paths, formulated along the process of constitution of the city. And doing of the city while space of interests and fights. The work appears for as the urban conflicts for the home, for the search of better life conditions, it puts in movement actions unchained by this population that they originate social demands that they belong to the place